2019
DOI: 10.18203/2394-6040.ijcmph20190207
|View full text |Cite
|
Sign up to set email alerts
|

Medicos: knowledge and attitude on Nipah at Malappuram district, India

Abstract: Background: A recent epidemic of Nipah virus affected few districts of Malabar in Kerala, Southern India. Eighteen people died, remarking case fatality rate of 94.7%. Early diagnosis within second case by doctors and prompt control activities by the health ministry saved more lives. Objective was to study knowledge and attitude about Nipah among medical students of Malappuram District.Methods: The study was conducted among 200 MBBS students of tertiary medical college at Malappuram district, North Kerala. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…In the present study more than half of the students were aware about the clinical features and complications of Nipah virus infection which was similar to a study conducted by Kanniyan et al among medical students in a medical college of Kerala. 3 A study done on the awareness regarding Ebola virus by Aliya et al, shows that about 63% of the students were aware about the mode of transmission, 50.6% of the students knew that Ebola virus disease can be diagnosed via ELISA. 53.2% of the students correctly identified that no treatment is available for Ebola virus disease as yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study more than half of the students were aware about the clinical features and complications of Nipah virus infection which was similar to a study conducted by Kanniyan et al among medical students in a medical college of Kerala. 3 A study done on the awareness regarding Ebola virus by Aliya et al, shows that about 63% of the students were aware about the mode of transmission, 50.6% of the students knew that Ebola virus disease can be diagnosed via ELISA. 53.2% of the students correctly identified that no treatment is available for Ebola virus disease as yet.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of the virus is very rapid and fatal, with a case fatality of 40-70%. 3 The transmission of NiV virus occurs from infected pigs to human (Malaysian NiV outbreak), infected bats to human (consumption of raw date palm sap contaminated with infectious bat excretions) and also human to human transmission (seen in the family and care givers of Nipah virus infected person). 4 There is no proven effective treatment at present and primary treatment is intensive supportive care.…”
mentioning
confidence: 99%
“…A similar study conducted by Kanniyan et al among medical students in a medical college of Kerala found that half of the students (51%) had good knowledge about Nipah. [5] In the wake of the outbreak, a better knowledge score was expected from the medical interns as Indian medical graduates should be lifelong learners.…”
Section: Discussionmentioning
confidence: 99%
“…In the above-mentioned study, the authors found that majority (70%) of the medical students had good attitude towards Nipah virus disease. [5]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation